(untitled) (KYAMC Journal, 2019)
Ewing’s sarcoma is a common malignancy of the bone and soft tissues in pediatric patients. It mostly affects the long bones and pelvis, and less commonly the flat bones and vertebrae. Primary Ewing’s sarcoma affecting the spine is very rare. The patient has non-specific symptoms for a prolonged period of time before the correct diagnosis is given. Patients can present with acute paraplegia due to spinal cord compression, which needs prompt surgical intervention. Early diagnosis and treatment are important for neurological recovery. The definitive management includes three main modalities: surgery, radiotherapy and combination chemotherapy. Adequate surgical excision may not be feasible because of anatomical limitations and local control is mainly achieved by radiotherapy. Because of the low incidence of these tumors, a multitude of therapeutic strategies have been employed with varying success. Currently there are no clinical guidelines outlining optimal management KYAMC Journal Vol. 10, No.-3, October 2019, Page 164-167